TOWARDS FAIR DIVISION OF BENEFITS FROM PATENT RIGHTS: REMUNERATION FOR EMPLOYEE-INVENTOR IN POLISH LEGAL SYSTEM AND IN COMPARATIVE CONTEXT - Krupa-Lipińska, Katarzyna (Torun International Studies, 2023)
Remuneration for the employee-inventor is the key element to stimulate the development both in business and academic units for the beneficiary of the whole society. The first element that should be taken into consideration in the given analysis is to whom right to obtain patent belong and later - in case the right to patent belong to employer - whether and how employee-inventor should be remunerated. Both of those problems are differently set in different jurisdictions. Polish law adhere to the systems which by statute prescribes right to obtain patent in case of employee inventions to employer and also by statue guarantee remuneration for employee-inventor both in business and academic environment. The conclusion of the article is that despite of the fact that the statutory provisions are reasonably and fairly constructed there in certain elements they are vague and left much space for the internal regulation of economic entities and higher educational institutions, which at the end of the day might change the overall assessment and work better for those entities than for the employees.